PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI DINAS PERTANIAN DAN PERKEBUNAN KABUPATEN KEDIRI - Amalia, Enggar Nuzzulul; Widodo, Eko; Muttaqien, Zaenul; Halim, Abdul (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
To create the success of the work of an employee, a leader must take a management step so that organizational goals can be achieved. The work environment, in the organization is also very influential on improving the performance of employees. Motivation in terms of someone's personality that encourages the desire of individuals to carry out certain activities to achieve goal of self satisfaction. Training for employees is a process of teaching activities knowledge and expertise to improve, and develop work competencies. The sample in this study is a saturated sample, meaning that all populations are sampled, namely all employees of the Department of Agriculture and Plantation of Kediri Regency as many as 50 people. With technical analysis of validity, reliability, multiple regression, R2, test F test hypotheses, t test and classical assumption test normality, multicolinerity test, hereroskedasticity test. And linearity test. All analyzes were done with SPSS software. The results of this study: 1) there is a significant influence between work environment (X1), motivation (X2) and training (X3) on employee performance (Y). This can be seen from the correlation value (R) of 0.899. 2) there is a significant influence between (X1) on employee performance (Y). This is evidenced by the results of the test t count (2,247) with a probability value (α) of 0.029 <0.05. 3) there is a significant influence between motivation (X2) on employee performance (Y). This can be proven by the test results t count (2.408) with a probability value (α) of 0.020 <0.05. 4) there is a significant influence between training (X3) on employee performance (Y). This is evidenced by the results of tcount (2.184) with a probability value (α) of 0.034 <0.05.